1995
DOI: 10.1128/cdli.2.1.104-114.1995
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CD4 cell count by a simple enzyme-linked immunosorbent assay using the TRAx CD4 test kit and by flow cytometry and hematology

Abstract: Measurement of CD4 T-lymphocyte levels is clinically useful in monitoring immune status in a number of conditions, including human immunodeficiency virus (HIV) infection, in which the absolute CD4 count is used to guide therapy. The absolute CD4 count is obtained by multiplying the results of the leukocyte count and the differential with a hematology cell counter and the percentage of CD4 ؉ T lymphocytes determined by flow cytometry. These techniques require expensive, complex instrumentation, and interlaborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…It is believed that the variability of this measurement (flow cytometry combined with WBC count and differential) could be lowered by using a direct measurement of the number of cells rather than a counting method with multiple steps. Other methods for performing CD4 cell counts require dedicated instruments (5,8) or kits that measure cell products or characteristics of groups of cells (3,9). Recently, methods for measuring cells directly from the flow cytometer have been developed (7) (Flow Count [Coulter Immunology], ImmunoCount [Ortho Diagnostics], and TruCount [Becton Dickinson Immunocytometry Systems]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that the variability of this measurement (flow cytometry combined with WBC count and differential) could be lowered by using a direct measurement of the number of cells rather than a counting method with multiple steps. Other methods for performing CD4 cell counts require dedicated instruments (5,8) or kits that measure cell products or characteristics of groups of cells (3,9). Recently, methods for measuring cells directly from the flow cytometer have been developed (7) (Flow Count [Coulter Immunology], ImmunoCount [Ortho Diagnostics], and TruCount [Becton Dickinson Immunocytometry Systems]).…”
Section: Discussionmentioning
confidence: 99%
“…Single-platform tests for determining the number of CD4 ϩ T cells have included simple technologies dedicated to obtaining absolute numbers for CD4 and CD8 T cells (3,5,8,9). Recently, tests that permit these measurements to be made di-rectly on clinical flow cytometers have been developed.…”
mentioning
confidence: 99%
“…After obtaining verbal informed consent, peripheral blood mononuclear cells (PBMCs) and plasma were isolated from venous blood collected in cell preparation CPT tubes (Becton Dickinson, Franklin Lakes, NJ) and stored at −70°C. CD4 + cell level was determined with the TRAx enzyme immunoassay as previously described [Paxton et al, 1995;Adu-Sarkodie et al, 1998].…”
Section: Materials and Methods Sample Collection And Storagementioning
confidence: 99%
“…The accurate enumeration of these cells both as absolute and percentage values remains crucial in providing care to HIV‐1–infected individuals and assessing new antiretroviral drugs and therapeutic vaccines. Previous studies on absolute counts have identified substantial variability in results between laboratories (4, 5). The introduction of multicolor immunophenotyping has made it possible to harness lineage‐specific markers (6, 7).…”
mentioning
confidence: 99%
“…It has been known for over a decade that the age of the blood sample has a significant impact on the accuracy and reproducibility of the T‐cell subset measured with the traditional lymphocyte gating technology (5). In this study, we assessed the impact of specimen aging (up to 4 days) on the absolute number and percentage of T‐cell subsets with four gating protocols.…”
mentioning
confidence: 99%